Animal Welfare New Insights - Hung, Shao-Wen; Chen, Chia-Chi; Lu, Chung-Lun; Kao, Tseng-Ting (Veterinary Medicine and Science, 2023)
Animal welfare has become a topic of serious discussion worldwide. Humane breeding has become an issue that has been given international attention in recent years. However, many people are still very unfamiliar with this concept. The foundation of humane feeding is based on AW. The main appeal is to allow animals to have five freedoms. When animal feeding meets these conditions, it can be regarded as meeting the basic requirements of humane feeding. The basis for the sustainable implementation of humane breeding is actually consumers. If consumers do not support the concept of humane feeding and do not agree with the price difference that should be paid for the production of humane products, then producers have no resources to put humane concepts into the production process. Therefore, only when consumers pay attention to humane production in terms of consumer behavior, more producers are willing to raise livestock and poultry in a humane way. As long as the insistence of both consumers and producers is satisfied, animals can be treated better.